Suizid Theologisch-diakoniewissenschaftliche Reflexionen - Schmidt, Markus (Wissenschaftliche Buchgesellschaft (wbg), 2023)
The pressure for a successful life is high. The old ideology of efficiency lives in people's heads, people ask the question every day: "Is it worthy to live like this?", or: "I don't want to die like this. It's unworthy." Since the judgment of the Federal Constitutional Court on February 26, 2020, there has been a discussion within diaconia, church and theology on how diaconal institutions for suicide assistance should behave. The task at hand is to develop a new legal situation. To this end, theology and diaconal studies have to stimulate in-depth reflection on the Christian image of man and sharpen the formation of ethical judgments. Suicide and assisted suicide have similarities and differences. The phenomenon needs to be looked at comprehensively, which requires biblical-theological investigations and fundamental-ethical considerations in order to develop practical-theological perspectives on suicide, assisted suicide and suicide prevention.